The Effect of Mobile Asset Management on the Safeguarding of Regional Property at the Sukabumi City Regional Secretariat - Siti Salsabila; Tuah Nur; Dian Purwanti (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study, titled The Influence of Movable Asset Management on the Security of Regional Government Property at the Regional Secretariat of Sukabumi City, aims to examine the extent to which movable asset management affects asset security effectiveness. The research applied a quantitative descriptive approach using an associative method. The sample consisted of 63 respondents selected through simple random sampling. Data were collected through questionnaires, interviews, observations, and documentation. The analysis revealed a moderate relationship between movable asset management and asset security, with a correlation coefficient of 0.576 and a determination coefficient of 33.2%. Simple linear regression resulted in the equation Y = 18.884 + 0.920X, while the t-test showed a significant influence of movable asset management on asset security (t-value 5.510 > t-table 1.999, sig. 0.000 < 0.05). The findings conclude that effective movable asset management enhances the security of regional assets in administrative, physical, and legal aspects. The study recommends improving data recording systems, enhancing inter-unit coordination, and strengthening human resource capacity in asset management practices.